Cognitive Impairment Predicts The Occurrence Of Hepatic Encephalopathy After Transjugular Intrahepatic Portosystemic Shunt. (April 2016) - Nardelli, Silvia; Gioia, Stefania; Pasquale, Chiara; Pentassuglio, Ilaria; Farcomeni, Alessio; Merli, Manuela; Salvatori, Filippo Maria; Nikolli, Leandra; Torrisi, Sabrina; Greco, Francesca; Nicoletti, Valeria; Riggio, Oliviero
Abstract : Objectives: Hepatic encephalopathy (HE) is a major problem in patients treated with TIPS. The aim of the study was to establish whether pre‐TIPS covert HE is an independent risk factor for the development of HE after TIPS. Methods: Eighty‐two consecutive cirrhotic patients submitted to TIPS were included. All patients underwent the PHES to identify those affected by covert HE before a TIPS. The incidence of the first episode of HE was estimated, taking into account the nature of the competing risks in the data (death or liver transplantation). Results: Thirty‐five (43%) patients developed overt HE. The difference of post‐TIPS HE was highly significant ( P =0.0003) among patients with or without covert HE before a TIPS. Seventy‐seven percent of patients with post‐TIPS HE were classified as affected by covert HE before TIPS. Age: (sHR 1.05, CI 1.02–1.08, P =0.002); Child–Pugh score: (sHR 1.29, CI 1.06–1.56, P =0.01); and covert HE: (sHR 3.16, CI: 1.43–6.99 P =0.004) were associated with post‐TIPS HE. Taking into consideration only the results of PHES evaluation, the negative predicting value was 0.80 for all patients and 0.88 for the patients submitted to TIPS because of refractory ascites. Thus, a patient with refractory ascites, without covert HE before a TIPS, has almost 90% probability of being free of HE after TIPS. Conclusions: Psychometric evaluation before TIPS is able to identify most of the patients who will develop HE after a TIPS and can be used to select patients in order to have the lowest incidence of this important complication.